PREDIKSI LAMA STUDI MAHASISWA DENGAN MENGGUNAKAN METODE K-NNPREDICTION OF STUDY TIMING PERIOD USING K-NNMETHOD - Deserius Marianus Oenunu; Naniek Widyastuti; Uning Lestari (Jurnal SCRIPT, 2015)
Quality of a university can be seen from study timing period. Development of data mining can be used to make predictions of study timing period. These research predictions of study timing period using data mining. The method used to make predictionsis K-Nearest Neighbour. A total 216students will be predicted into 3 classes: Very On Time, On Time and Not On Time. From the experimental results, the obtained value of the highest accuracyreaches80% when the data training 186with a value of k=30